Effectiveness of Physiotherapy in Alleviating Musculoskeletal Pain During Pregnancy: A Literature Review - Anisah, Mutiara; Fatmarizka, Tiara (Majalah Ilmiah Fisioterapi Indonesia; Vol 13 No 2 (2025): Majalah Ilmiah Fisioterapi Indonesia, 2025)
Background: Pregnancy leads to anatomical and physiological changes that frequently cause musculoskeletal complaints, particularly in the third trimester. Common issues include low back pain and pelvic girdle pain, which may interfere with daily activities and reduce the quality of life and psychological well-being of pregnant women. Physiotherapy offers targeted interventions to reduce pain and improve physical function during pregnancy. Methods: This study is a literature review based on searches conducted in PubMed, Google Scholar, PEDro, and Scopus databases. The keywords used included “pregnancy,” “musculoskeletal,” “low back pain,” “pelvic girdle pain,” and “carpal tunnel syndrome.” The PRISMA flow diagram was used to guide the selection process. Inclusion criteria consisted of randomized controlled trials (RCTs) involving pregnant women over 18 years of age experiencing musculoskeletal pain and receiving physiotherapy interventions. Studies were excluded if they were non-RCTs, involved non-pregnant participants, or lacked full-text access. Eligible articles were analyzed using a synthesis matrix. Results: The review found that physiotherapy interventions, including Pilates, aerobic exercise, aquatic therapy, stabilization, strengthening, and stretching exercises, were effective in reducing musculoskeletal pain and disability while improving mobility and physical function. Most studies reported significant improvements following consistent physiotherapy during pregnancy. Conclusion: Physiotherapy is effective in managing musculoskeletal pain among pregnant women. Interventions such as Pilates, aerobic, and aquatic exercises provide notable benefits in reducing discomfort and enhancing functional capacity. These therapies should be considered for integration into antenatal care programs to support maternal health and quality of life. Keywords: Pregnancy, musculoskeletal, low back pain, pelvic girdle pain, lumbopelvic pain, carpal tunnel syndrome